2008
DOI: 10.1086/529043
|View full text |Cite
|
Sign up to set email alerts
|

Primary Vaccine Failure after 1 Dose of Varicella Vaccine in Healthy Children

Abstract: Universal immunization of young children with 1 dose of varicella vaccine was recommended in the United States in 1995, and it has significantly decreased the incidence of chickenpox. Outbreaks of varicella, however, are reported among vaccinated children. Although vaccine effectiveness has usually been 85%, rates as low as 44% have been observed. Whether this is from primary or secondary vaccine failure-or both-is unclear. We tested serum samples from 148 healthy children immunized against varicella in New Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
3
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 41 publications
1
97
3
4
Order By: Relevance
“…However, a recent study showed a seroconversion rate in susceptible healthy children of 76% after one dose of VV (24), suggesting that one dose of this vaccine could lead to primary vaccine failure. In fact, the last published guidelines on VV from the Centers for Disease Control and Prevention (June 2007) advocated the use of 2 doses of the vaccine for all children after 1 year of age, independently of the immunologic situation (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed a seroconversion rate in susceptible healthy children of 76% after one dose of VV (24), suggesting that one dose of this vaccine could lead to primary vaccine failure. In fact, the last published guidelines on VV from the Centers for Disease Control and Prevention (June 2007) advocated the use of 2 doses of the vaccine for all children after 1 year of age, independently of the immunologic situation (14).…”
Section: Discussionmentioning
confidence: 99%
“…It is highly sensitive because the preservation of the structure of the surface glycoproteins on infected cells allows neutralising antibodies to be detected [389] . It has been used to assess protection against varicella as a value of ≥ 4 correlates with protection [215,347,376,[390][391][392] . Its limitations are that it is semi-quantitative, cannot be automated, and requires specialised personnel and specific equipment; reading is subjective and subject to inter-laboratory variability [30] .…”
Section: Ifamentioning
confidence: 99%
“…Истинная иммунная прослойка рассчитывается вычитанием из привитых и переболевших детей доли серонегативных (по напряженности иммунитета в выбор-ке) лиц [26]. Мировой опыт исследования эффективности ветряночной вакцины свидетельствует, что около 15% детей, получивших однодозовую иммунизацию, остаются серонегативными и подвержены развитию «ветрянки прорыва» вследствие первичной или вторичной вакци-нальной недостаточности [27,28]. По вышеозначенным причинам определение истинной иммунной прослойки в домах ребенка не представляется возможным.…”
Section: фармакоэкономика в педиатрииunclassified